POLITIK HUKUM UNDANG-UNDANG CIPTA KERJA - Yulianto, Wachid; Erofa, Andi (P3M dan Jurusan Syariah dan Ekonomi Bisnis Islam STAIN Sultan Abdurrahman Kepulauan Riau, 2023)
Omnibus law or omnibus bill is the practice of drafting laws and regulations with countries that adhere to the common law tradition. In Indonesia's legal system with the civil law tradition, the preparation of laws and regulations using the omnibus method is a step that is considered to be able to overcome hyper regulation and disharmony of existing laws. With all the controversy over the formation of the UU No. 11/2020, the government emphasizes that this Law is believed to be able to revive the economy and investment from within the country and abroad. In fact, the pros and cons of drafting UU No. 11/2020 have, in fact, been submitted to the Constitutional Court for a judicial review, both in terms of formal and material trials. With the